Effects of taper on swimming force and swimmer performance after an experimental ten-week training program - Papoti, Marcelo [UNESP]; Martins, Luis E.B.; Cunha, Sergio A. [UNESP]; Zagatto, Alessandro M. [UNESP]; Gobatto, Claudio A. [UNESP] (My University, 2007)
Papoti, M., L.E.B. Martins, S.A. Cunha, A.M. Zagatto, and C.A. Gobatto. Effects of taper on swimming force and swimmer performance after an experimental ten-week training program. J. Strength Cond. Res. 21(2):538-542. 2007.- The purpose of this research was to examine how an 11-day taper after an 8.5-week experimental training cycle affected lactate levels during maximal exercise, mean force, and performance in training swimmers, independent of shaving, psychological changes, and postcompetition effects. Fourteen competition swimmers with shaved legs and torsos were recruited from the São Paulo Aquatic Federation. The training cycle consisted of a basic training period (endurance and quality phases) of 8.5 weeks, with 5,800 m·d -1 mean training volume and 6 d·wk -1 frequency; and a taper period (TP) of 1.5 weeks' duration that incorporated a 48% reduction in weekly volume without altering intensity. Attained swimming force (SF) and maximal performance over 200m maximal swim (Pmax) before and after taper were measured. After taper, SF and Pmax improved 3.6 and 1.6%, respectively (p < 0.05). There were positive correlations (p < 0.05) between SF and Pmax before (r = 0.86) and after (r = 0.83) the taper phase. Peak lactate concentrations after SF were unaltered before (6.79 ± 1.2 mM) and after (7.15 ± 1.8 mM) TP. Results showed that TP improved mean swimming velocity, but not in the same proportion as force after taper, suggesting that there are other factors influencing performance in faster swimming. © 2007 National Strength & Conditioning Association.
Keywords: Lactate; Periodization; Training; lactic acid derivative; adolescent; blood; ergometry; female; fitness; human; male; methodology; muscle strength; physical education; physiology; swimming; Adolescent; Ergometry; Female; Humans; Lactates; Male; Muscle Strength; Physical Education and Training; Physical Fitness; Swimming